THE ROLE OF MYCORRHIZAL FUNGI IN SOME AGRICULTURAL CROPS (Experimental biology, 2016)
The article discusses about mikotrophic active development of arbuscular-vesicular mycorrhizae. Studies showed the high mycorrhizal activity in plant species with mycorrhizae, as well as the relationshipbetween mikotrophic level and harvest.
Keywords: arbuscular-vesicular micorrhizae; crops; endomicorrhizae; intensity of a mikotrophic; productivity